Improving Teacher Competence in Supporting the Achievement of Basic Education Goals - Yelfianita, Yelfianita; S, Neviyarni; Irdamurni, Irdamurni (International Journal of Educational Dynamics, 2023)
Improving teacher competence plays a crucial role in achieving optimal goals in basic education. This article aims to discuss the importance of enhancing teacher competence in supporting the achievement of basic education goals. The study adopts a qualitative approach, utilizing interviews with six teachers and a literature review consisting of articles. The research procedure involves data collection through in-depth interviews with teachers and literature analysis to identify factors influencing teacher competence. The findings indicate that a deep understanding of the subject matter, the use of innovative teaching methods, effective classroom management skills, and professional development for teachers are essential factors in improving teacher competence. Furthermore, suggested strategies and initiatives include professional development programs, collaboration among teachers, effective supervision and mentoring, optimizing the use of supportive resources, and developing comprehensive assessment systems. It is emphasized that serious attention from the government and educational institutions is crucial in enhancing teacher competence to improve the quality of basic education and provide a better future for the next generation.